The relationship between social supports on mental health among university students in Klang Valley - Amin, Samir Muhazzab; Ibrahim, Nor Fatimahwati; Nazuri, Nur Shuhamin; Ahmad Suhaimi, Siti Shazwani (Human Resources Management Academic Research Society (HRMARS), 2024)
This study aimed to investigate the relationship between social support and mental health among university students in Klang Valley. A total of 357 students from Universiti Putra Malaysia (UPM), Universiti Kebangsaan Malaysia (UKM), and Universiti Malaya (UM) participated, selected through stratified sampling. Data were collected using self- administered questionnaires, including the Social Support Questionnaire (SSQ) by Sarason et al. (1987) and the Depression Anxiety Stress Scale (DASS-21) by Lovibond & Lovibond (1995). The results indicated a negative correlation between social support and mental health. Family support, friends support, and teachers support also showed negative correlations with mental health. Students' mental health levels were evaluated, showing moderate depression, severe anxiety, and mild stress. The study concluded that family and teacher support are significant predictors of mental health, with family support being the strongest. Friends' support was not a significant predictor. To improve students' mental well-being, the role of the counseling department and student affairs should be intensified through mental health awareness programs. Future studies should include more universities and larger sample sizes for better generalizability and reliability.